Channel slope, flow width, flow depth, hillslope angle, unit stream power for the trunk streams in Iwaki, Japan - Takahashi, Naoya (PANGAEA, 2023)
Longitudinal channel slope, flow width and depth at a high-flow stage, average hillslope angles along a trunk stream, and unit stream power are included in this data. These data were collected in the trunk streams along the Yunodake fault in Iwaki city, Japan. Channel slope is calculated using 10-meter meshed digital elevation model obtained from the Geospatial Information Authority of Japan. Flow width and depth were measured during June-August in 2019. Flow width was measured using a laser range-finder, TruPulse 360 (Laser Technology, Inc.). Flow depth was measured using a staff. Average hillslope angles were calculated using 5-meter meshed digital elevation model obtained from the Geospatial Information Authority of Japan. These data were collected to investigate the variation of channel and hill slope morphologies along streams and their response to an increase in channel incision rates.
Keywords: Bedrock river; Hydraulic geometry; Unit stream power